Perancangan Alat Monitoring Gas Medis N2O Berbasis ESP32 - Setyo Adi Nugroho (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Medical gas installation is an important aspect in which gas availability must always be maintained and guaranteed. One of the monitored gases is N2O gas. The medical gas monitoring system must always be carried out regularly, but sometimes in conditions in the field there are still many medical gas monitoring systems that still use analog manometers so that the results obtained are sometimes inaccurate so that it can cause a condition that is dangerous for the patient. Then a digital monitoring system was created that could display in real time using the SKU237545 sensor and the ESP32 microcontroller as the center of the system that processes data. The test results from the tool that has been made get the largest error of 0.08% at a pressure of 2 Bar and the smallest error of 0.01% at a pressure of 4, 5 and 6 Bar and the purity of N2O gas is not affected by the size of the pressure. Thus this tool is feasible to use because the work system is in accordance with the conditions and conditions of the existing tools in the field.